Prevalence and prognosis of ischaemic and non-ischaemic myocardial fibrosis in older adults - Shanbhag, Sujata M; Greve, Anders M; Aspelund, Thor; Schelbert, Erik B; Cao, J Jane; Danielsen, Ragnar; Þorgeirsson, Guðmundur; Sigurðsson, Sigurður; Eiríksdóttir, Guðný; Harris, Tamara B; Launer, Lenore J; Guðnason, Vilmundur; et al. (European heart journal, 2019)
Non-ischaemic cardiomyopathies (NICM) can cause heart failure and death. Cardiac magnetic resonance (CMR) detects myocardial scar/fibrosis associated with myocardial infarction (MI) and NICM with late gadolinium enhancement (LGE). The aim of this study was to determine the prevalence and prognosis of ischaemic and non-ischaemic myocardial fibrosis in a community-based sample of older adults. The ICELAND-MI cohort, a substudy of the Age, Gene/Environment Susceptibility Reykjavik (AGES-Reykjavik) study, provided a well-characterized population of 900 subjects after excluding subjects with pre-existing heart failure. Late gadolinium enhancement CMR divided subjects into four groups: MI (n = 211), major (n = 54) non-ischaemic fibrosis (well-established, classic patterns, associated with myocarditis, infiltrative cardiomyopathies, or pathological hypertrophy), minor (n = 238) non-ischaemic fibrosis (remaining localized patterns not meeting major criteria), and a no LGE (n = 397) reference group. The primary outcome was time to death or first heart failure hospitalization. During a median follow-up of 5.8 years, 192 composite events occurred (115 deaths and 77 hospitalizations for incident heart failure). After inverse probability weighting, major non-ischaemic fibrosis [hazard ratio (HR) 3.2, P < 0.001] remained independently associated with the primary endpoint, while MI (HR 1.4, P = 0.10) and minor non-ischaemic LGE (HR 1.2, P = 0.39) did not. Major non-ischaemic fibrosis was associated with a poorer outcome than MI (HR = 2.3, P = 0.001) in the adjusted analysis. Major non-ischaemic patterns of myocardial fibrosis portended worse prognosis than no fibrosis/scar in an older community-based cohort. Traditional risk factors largely accounted for the effect of MI and minor non-ischaemic LGE.